2021
DOI: 10.1186/s13018-021-02528-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF-A Signaling Pathway in Cartilage of ACLT-induced Osteoarthritis Mouse Model

Abstract: Background Anterior cruciate ligament transection surgery (ACLT)-induced OA model was often used to investigate the molecular mechanism of knee osteoarthritis (KOA). Researches have shown that vascular endothelial growth factor (VEGF) played an important role in OA. The present study aimed to investigate the pathological changes after ACLT surgery and reveal the expression characteristics of the VEGF-A/VEGFR2 signaling pathway in this model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…32 ACLT induced degradation of articular cartilage was time-dependent, and many inflammation factors including nitric oxide (NO) and vascular endothelial growth factor (VEGF) were positively correlated with the degree of KOA. 33 Time points for in vivo OA monitoring were conducted in accordance with the timeline in Fig. 4(A).…”
Section: Resultsmentioning
confidence: 99%
“…32 ACLT induced degradation of articular cartilage was time-dependent, and many inflammation factors including nitric oxide (NO) and vascular endothelial growth factor (VEGF) were positively correlated with the degree of KOA. 33 Time points for in vivo OA monitoring were conducted in accordance with the timeline in Fig. 4(A).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest the local administration of bevacizumab for the treatment of disc degeneration has potential clinical application. Some studies have observed a relationship between VEGF and chondrocytes in terms of physiology and pathology (Chen et al, 2019;Qian et al, 2021;Xiao et al, 2021;Xiaoshi et al, 2021), but there was a lack of relevant studies in IVD. We found that VEGF is highly expressed in IDD of humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed a relationship between VEGF and chondrocytes in terms of physiology and pathology ( Chen et al, 2019 ; Qian et al, 2021 ; Xiao et al, 2021 ; Xiaoshi et al, 2021 ), but there was a lack of relevant studies in IVD. We found that VEGF is highly expressed in IDD of humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Qian et al. 63 established a moderate mouse KOA model using ACLT, and hematoxylin–eosin (HE) and safranin‐O (S‐O) staining were used to detect pathological changes in knee cartilage at 1, 2, 4, 8, and 12 weeks after surgery. It was found that the characteristics of cartilage degeneration in mice were time dependent and the expression of inflammatory factors was high, which were basically consistent with the degree of KOA, ensuring the success of the model.…”
Section: Methods Of Establishing Koa Animal Modelsmentioning
confidence: 99%